The chosen aspects of real-time collaborative editing of electronic documents - Wójtowicz, Radosław (Wybrane aspekty grupowego redagowania dokumentów elektronicznych w czasie rzeczywistym, 2011)
The article presents a few problems of electronic documents collaborative editing. The main purpose of the article is to gather and explain the most significant notions in the described area, and to identify the major problems in the realm of creation and use of the software supporting collaborative creating and editing documents, as well as to present a synthetic overview of the modern market of such systems
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 205, s. 270-280
Keywords: electronic document management system; document management; electronic document; collaborative editing; real-time collaborative editing